2002
DOI: 10.1016/s0022-5347(05)65334-7
|View full text |Cite
|
Sign up to set email alerts
|

Heredity of Hypospadias and the Significance of Low Birth Weight

Abstract: We present data on heredity, birth weight, phenotype and ethnic origin in a large group of patients with hypospadias. The finding of additional members with hypospadias in 7% of the families supports the concept that genetic factors are involved in the pathogenesis. The strong association with low birth weight may be explained by genetic and environmental factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
47
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(54 citation statements)
references
References 26 publications
7
47
0
Order By: Relevance
“…Previous studies have reported ethnic variations in the occurrence of cryptorchidism and hypospadias (Chia et al 2003; Fredell et al 2002). Familial aggregation has been described for both abnormalities, supporting the importance of genetic factors (Fredell et al 2002; Weidner et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported ethnic variations in the occurrence of cryptorchidism and hypospadias (Chia et al 2003; Fredell et al 2002). Familial aggregation has been described for both abnormalities, supporting the importance of genetic factors (Fredell et al 2002; Weidner et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…One study retrospectively compared the birth weights of boys in Sweden who had been operated on for hypospadias with that of their brothers without hypospadias, thus correcting for genetic potential [14]. Boys with hypospadias were found to have birth weights on average 100 g lower than their healthy brothers.…”
Section: Hypospadiasmentioning
confidence: 99%
“…However, the factors that contribute to the risk of one monozygotic twin suffering from hypospadias are as yet unknown. Fredell et al [14] have suggested that this increased risk may be due to a relative insufficiency of human chorionic gonadotrophin, resulting in an inability of the placenta to produce sufficient levels of androgens for both twins.…”
Section: Hypospadiasmentioning
confidence: 99%
“…The risk of siblings also having hypospadias is about 4.2%. 27 In conclusion, the HES data were of high quality for the study period. Data on correctional procedures were used to assess prevalence trends.…”
Section: Discussionmentioning
confidence: 82%